Growth and thermal properties of doped monocrystalline titanium-silicide based quantum dot superlattices. (April 2016) - Savelli, G.; Silveira Stein, S.; Bernard-Granger, G.; Faucherand, P.; Montès, L.
Abstract: This paper presents the growth mechanism of a monocrystalline silicide quantum dot superlattices (QDSL) grown by reduced pressure chemical vapor deposition (RPCVD). QDSL are made of TiSi2 -based nanodots scattered in a p-doped Si90 Ge10 matrix. It is the first time that the growth of a p-type monocrystalline QDSL is presented. We focus here on the growth mechanisms of QDSL and the influence of nanostructuration on their thermal properties. Thus, the dots surface deposition, the dots embedding mechanisms and the final QDSL growths are studied. The crystallographic structures and chemical properties are presented, as well as the thermal properties. It will be shown that some specific mechanisms occur such as the formation of self-formed quantum well superlattices and the dopant accumulation near the quantum dots. Finally, a slight decrease of the QDSL thermal conductivity has been measured compared to the reference sample. Highlights: Titanium-based silicide Quantum Dot Superlattice is grown by industrial Chemical Vapor Deposition reactor. P-type monocrystalline structure has been elaborated. Chemical study is presented highlighting the dots formation and growth mechanisms. Thermal properties have been measured highlighting the influence of nanostructuration.